Global Modernity - Schmidt, V. author. aut Link
X, 110 p.
Keywords: This book introduces the concept of global modernity as a paradigm for the analysis of the contemporary era. Building on Parson's distinction between social, cultural, personal and organismic systems, it presents a four-dimensional scheme that aims to identify modernity's key structural components.